2009
DOI: 10.1364/oe.17.018148
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal bessel beams: theory and experiments

Abstract: We describe a family of dispersion-free and diffraction-free optical beams consisting in two-dimensional wave packets with a spatiotemporal Bessel (STB) profile propagating in media with anomalous dispersion. We also describe quasi-invariant optical beams with a spatiotemporal Bessel-Gauss (STBG) profile; these wave packets have finite dimensions and energy, conditions to be representative of physical beams. The paper provides a detailed account of the properties of STB and STBG beams, including their spatiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 18 publications
1
52
0
Order By: Relevance
“…The last point is supported by the existence, as mentioned before, of the 2D spatially localized BB, or of the 2D STBB characterized in [18], both stationary in propagation. In both cases, the ringlike spatial spectrum of the BB or the ringlike spatiotemporal spectrum of the STBB leads to a Bessel profile in the near field, and to its localization in space and in space-time, respectively.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…The last point is supported by the existence, as mentioned before, of the 2D spatially localized BB, or of the 2D STBB characterized in [18], both stationary in propagation. In both cases, the ringlike spatial spectrum of the BB or the ringlike spatiotemporal spectrum of the STBB leads to a Bessel profile in the near field, and to its localization in space and in space-time, respectively.…”
Section: Introductionsupporting
confidence: 53%
“…A similar stationary propagating WP is the two-dimensional spatiotemporal Bessel beam (STBB), also featured by infinite energy [18]. Analogously, the three-dimensional X waves and O waves are stationary wave packets in linear media when having unlimited energy [3][4][5][6]8,9].…”
Section: Introductionmentioning
confidence: 99%
“…By controllably associating each with a unique , programmable correlations are introduced into the ST-spectrum � ( , ). Recombining the spectrum via a second grating reconstitutes the pulse and simultaneously overlaps all the spatial frequencies, so the ST-beam is immediately realized along with no need for a spatial Fourier transform 40,41 .…”
Section: Methodsmentioning
confidence: 99%
“…But, they require a nonlinearity to preserve their shape. It was pointed out by Durnin that nonlinearity is not a necessity for invariant propagation; indeed, he proved that Bessel beams can propagate in a purely linear material without deformation (Durnin, 1987;Dallaire et al, 2009). On the other hand, Lopez and Helmerson have recently demonstrated that non-diffracting beams with arbitrary transverse shapes can be generated (Lopez-Mariscal and Helmerson, 2010).…”
Section: Introductionmentioning
confidence: 99%